INVENTORY OF INFORMATION SYSTEM DESIGN IN THE KGK MP IAIN JAKARTA USING MICROSOFT VISUAL BASIC 6.0 - Tohari Tohari; Ir. Fitri Sjafrina, MMSi (Jurnal Sistem Informasi, 2002)
KGK MP IAIN Jakarta is a cooperative engaged in the business that provides goodsstores and community needs of the members generally. But there are still deficienciesin its management in dealing with inventory records, providing information andreport the number of stock items. Therefore it is necessary to design the inventorysystem at the cooperative.Based on the analysis and the constraints faced in designing this system is therecording is still done manually, causing difficulty in checking inventory and the longpreparation of reports. Hopefully, with this new system can assist the work inaccordance with the expectations of the cooperative.